2014
DOI: 10.3748/wjg.v20.i7.1635
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of gastric cancer

Abstract: The authors focused on the current surgical treatment of resectable gastric cancer, and significance of peri- and post-operative chemo or chemoradiation. Gastric cancer is the 4(th) most commonly diagnosed cancer and the second leading cause of cancer death worldwide. Surgery remains the only curative therapy, while perioperative and adjuvant chemotherapy, as well as chemoradiation, can improve outcome of resectable gastric cancer with extended lymph node dissection. More than half of radically resected gastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
433
0
13

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 549 publications
(460 citation statements)
references
References 104 publications
2
433
0
13
Order By: Relevance
“…Tumors located in the distal part of the stomach are commonly treated by subtotal gastrectomy and reconstruction of digestive continuity. However, tumors located at the middle or proximal (cardia) part of the stomach may require total gastrectomy or esophagogastrectomy, if extended into the lower esophagus, resulting in a relatively worse prognosis [39][40][41][42]. Previous studies have shown that patients from Western countries have a significantly higher proportion of cardia tumors, while patients in Asia have a higher proportion of non-cardia gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors located in the distal part of the stomach are commonly treated by subtotal gastrectomy and reconstruction of digestive continuity. However, tumors located at the middle or proximal (cardia) part of the stomach may require total gastrectomy or esophagogastrectomy, if extended into the lower esophagus, resulting in a relatively worse prognosis [39][40][41][42]. Previous studies have shown that patients from Western countries have a significantly higher proportion of cardia tumors, while patients in Asia have a higher proportion of non-cardia gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of gastric cancer currently involves combinatorial therapies, including surgery, chemotherapy and radiotherapy; however, long-term survival rates remain relatively low (3,23). TNM classification based on the clinicopathological characteristics of tumors; including local invasive depth, lymph node involvement, and distant metastasis is the current gold standard for prognosis prediction and available Table II.…”
Section: Discussionmentioning
confidence: 99%
“…Despite developments in surgery, chemotherapy and radiation therapy, the prognosis of gastric cancer at advanced stages remains unsatisfactory, primarily due to tumor recurrence, local invasion and metastasis (5). The 5-year survival rate of patients with gastric cancer is <10% (6). Understanding the molecular mechanisms underlying the regulation of gastric cancer occurrence and development is necessary in order to identify novel and effective therapeutic methods to improve treatment outcome.…”
Section: Introductionmentioning
confidence: 99%